Resource Constraints: Teachers' Challenges in Implementing Digital Curriculum in Remote Areas - Komala, Imas; Wardani, Yulinda Ari; Khairiyah, Ayu; Arifin, Bahri (Raudhah Publisher, 2025)
The implementation of a digital curriculum in remote areas faces various challenges, particularly regarding resources. Teachers, as the front line of education, encounter difficulties such as limited technological infrastructure, lack of training, and restricted access to devices and internet networks. This study aims to identify the main obstacles teachers face in implementing the digital curriculum in remote areas and propose potential solutions to overcome these challenges. Using a qualitative approach, this research analyzes teachers' experiences through interviews and case studies. The findings indicate that a lack of technical support, financial resources, and supportive policies are the primary barriers to digital curriculum implementation. Therefore, interventions from various stakeholders, including the government and educational institutions, are necessary to enhance infrastructure readiness and teachers' competencies to ensure the successful implementation of the digital curriculum in remote areas.